Noisy green train - King, Sue (Brimax Rowville, Vic., 2007)
Little hands can turn the sturdy pages to read stories of a working day. Children will have fun making all the sounds of the train station, the city, the building site and the farm. Titles include Big Blue Truck, Little Red Tractor, Noisy Green Train and Strong Yellow Digger